2008
DOI: 10.1093/eurpub/ckn127
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and cost of treatment of genital warts in Spain

Abstract: This study provides a first overview of the burden of GW in Spain. A quadrivalent HPV vaccine that prevents HPV 6, 11, 16, 18 related diseases will have the potential to significantly decrease the socio-economic burden associated with GW in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 14 publications
4
66
2
5
Order By: Relevance
“…However, in a 2011 trial, performed in our country, the prevalence of genital papilloma was detected to be 154 and even as high as 326 in some regions per 100.000. In 2003 and 2004 US trials, this rate was 170-205 while a 2008 Spanish trial revealed a rate of 182.1, which was similar to Turkish rates (Insinga et al, 2003;Koshiol et al, 2004;Castellsague et al, 2008). Although the incidence of genital papilloma is similar, the lower incidence of cervical cancer which occurs due to the causes is controversial.…”
Section: Discussionmentioning
confidence: 98%
“…However, in a 2011 trial, performed in our country, the prevalence of genital papilloma was detected to be 154 and even as high as 326 in some regions per 100.000. In 2003 and 2004 US trials, this rate was 170-205 while a 2008 Spanish trial revealed a rate of 182.1, which was similar to Turkish rates (Insinga et al, 2003;Koshiol et al, 2004;Castellsague et al, 2008). Although the incidence of genital papilloma is similar, the lower incidence of cervical cancer which occurs due to the causes is controversial.…”
Section: Discussionmentioning
confidence: 98%
“…No entanto, estes estudos variam tanto na metodologia, como na apresentação dos dados, dificultando a apreciação do impacto global das IST por HPV. 5,[11][12][13] Como exemplo, em 1997, Munk et al reportaram uma prevalência de CAG de 17% nas mulheres entre os 17 -24 anos na Dinamarca. 9 Em 2007, um estudo multicêntrico, envolvendo países nórdicos (amostra de 70 000 mulheres), mostrou uma prevalência de 10,6% de CAG ao longo da vida.…”
Section: Discussionunclassified
“…7 Factores de risco conhecidos da infeção por HPV são: início precoce da vida sexual, múltiplos parceiros, história de outras infeções sexualmente transmissíveis (IST), tabagismo e gravidez precoce. 7 Em outubro de 2008, a vacina quadrivalente (genótipos 6,11,16,18) foi introduzida no plano nacional de vacinação de Portugal (PNV), com indicação para adolescentes com 13 anos. Associadamente, entre 2009 e 2011, decorreu uma campanha de vacinação para mulheres com 17 anos.…”
unclassified
“…It is estimated that warts represent the result of only a fraction of HPV infections and populations studies showed a prevalence of 0.6-1.5 up to 4-13 % in relation to sexual behavior [48,56,15]. Warts can develop in 2-3 months and 20-30 % of them regress spontaneously, but in about one-third of cases can recur [23,22].…”
Section: Related Pathologiesmentioning
confidence: 99%